Relative Evaluation of the Quantitative Aspects of the Websites of the Top Ten Oldest National Institute of Technology (NITs) in India through the Application of Webometric Parameters - Chakraborty, Indranil; Thakuria, Abhijit (Journal of Information and Knowledge, 2023)
A website serves as a gateway to any information about any institution in the present-day digital era. Webometrics is a technique of estimating the effectiveness and efficacy of a website by quantitative analysis of its links and webpages. In this study, the websites of the top ten oldest NITs (as per their year of Foundation as Regional Engineering College) were considered for webometric analysis. It was found that all the ten studied NIT websites have .ac.in as their URL extension. While NIT Kurukshetra has the most linked web pages, NIT Nagpur has the highest number of web pages on its website. After analysis it was revealed that NIT Kurukshetra has the highest Simple Web Impact Factor, Self-Link Web Impact Factor, External Link Web Impact Factor and Revised Web Impact Factor and clinched the top rank out of all the ten studied NIT websites. Though presence of broken links is found to be the maximum number on the NIT Kurukshetra website. From the estimation of the correlation between the Simple Web Impact Factor and the Revised Web Impact Factor, it was found that both variables have a coefficient of correlation of +0.28 in magnitude. This indicates that both the variables have a positive correlation between them. Hence out of all the ten NIT websites the website of NIT Kurukshetra is found to be most effective and efficient.